IMPLEMENTASI NILAI PENDIDIKAN KARAKTER PADA PEMBELAJARAN BIOLOGI DI SEKOLAH MENENGAH ATAS - Atira Elpariska Maya; Siti Huzaifah; Kodri Madang (Biosfer: Jurnal Pendidikan Biologi, 2017)
This research aims to describing the implementation of character education value in Biology lesson at Senior High School in Muara Enim Regency in respect to planning and implementation aspects of learning. The research subjects consisted of three Biology teachers determined by purposive sampling technique. Data collection techniques are used audiovisual materials and documents. Data were analyzed by transcription, coding and verifying data. the results of this research show that the implementation of character education value in Biology lesson on the aspect of planning and implementation consists of three things, namely 1) the values ​​designed and implemented by Biology teachers consists of discipline, curiosity, and responsibility, 2) values ​​designed but not implemented are discipline, creative value, curiosity value, and joy of reading, and 3) values ​​that are not designed but implemented are discipline, hard work, reading, and responsibility. In general, Biology teachers are implemented character education value in learning through messages by using words. In addition, Biology teachers also have not utilized the learning materials at each meeting to develop the value of character education of the learners.